Re-examining “the Book” through Ancient Egyptian Tomb Walls - Algarvio, Chana (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2023)
This article investigates how the seminal focus placed on portability as the defining characteristic of the book is erroneous and misguided. Based on Western concepts and early-modern bias that ultimately equates codex to book, the notion of portability is inapplicable to all book cultures and deserves re-examination. By redefining the meaning of the book to be an idea, an idea that can then be transposed textually and/or pictorially onto a substrate, scholars can come to understand how in ancient Egypt wall inscriptions and art were considered books, and how stone was a primary and fundamental book medium. Using Western, modern, and even global examples to explain how the book in its original state is a metaphysical entity, the notion of the book as object is in turn discarded because defining the book by its medium causes numerous restrictions – the object is not the book, merely its carrier. The importance of physical portability therefore becomes replaced in favour of metaphysical portability and its various implications. By using ancient Egyptian tomb walls as a case study, the meaning and boundaries placed on the book in book studies will be reframed and redefined by drawing Egyptian cultural practices, literature, ideologies, and the use of stone to establish examples of non-portable books. Any discussion of ancient book cultures primarily remains focused on papyrus or clay tablets (i.e., portable materials), a focus that skews the reality of ancient book cultures and gives rise to bias due to the neglect of other mediums that were far more important for ideological purposes. Egyptian book culture was, in fact, more than papyrus; a variety of materials were used as substrates, not all of which were portable in the conventional sense, but neither their use nor their significance to ancient Egyptian society should be dismissed.